Problematika Sosial Ujaran Kebencian (Hate Speech) Pada Generasi Milenial - Wulandari, Junita; Ulfah, Ulfah; Saputra, Anton; Zulkarnain, Ali Iskandar (Interdisciplinary Explorations in Research Journal, 2024)
Abstract The aim of this research is to determine awareness of using social media so that conflicts do not arise when using it. The method used in this research is a library research method sourced from books, articles and journals. By discussing this article, it is hoped that the millennial generation will be more conscious in using social media, such as selecting and selecting comments so as not to cause division or conflict. However, hate speech can also occur at school and in the community. Therefore, it is important for us to respect each other in social life. Keywords: Hate speech, social. Abstrak Tujuan penelitian ini adalah untuk mengetahui kesadaran bermedia sosial agar tidak timbul konflik dalam menggunakannya. Metode yang digunakan dalam penelitian ini merupakan metode kajian pustaka (Library Research) yang bersumber dari buku serta artikel dan jurnal. Dengan pembahasan artikel ini diharapkan kepada para generasi milenial agar dapat lebih sadar dalam menggunakan media sosial, seperti memilah dan memilih dalam berkomentar agar tidak menimbulkan perpecahan atau konflik. Namun, ujaran kebencian juga bisa terjadi di sekolah maupun di lingkungan masyarakat. Oleh karena itu, penting bagi kita untuk saling menghormati satu sama lain dalam kehidupan bersosial. Kata Kunci: Ujaran kebencian, sosial.